The Schocken Bible / Vol. 2 The early prophets : Joshua, Judges, Samuel, and Kings / a new transl. with introd., comment., and notes by Everett Fox - Fox, Everett (The Schocken Bible, 2014)
"The story of ancient Israel, from the arrival in Canaan to the destruction of the Kingdom of Judah and the Babylonian exile some six centuries later: the highly anticipated second volume in Everett Fox's landmark translation of the Hebrew Bible"--